MicroLet-7b Regulates Neutrophil Function and Dampens Neutrophilic Inflammation by Suppressing the Canonical TLR4/NF-κB Pathway - Chen, Binzhen; Han, Jia; Chen, Shaoheng; Xie, Rufeng; Yang, Jie; Zhou, Tongming; Zhang, Qi; Xia, Rong (Frontiers in Immunology, 2021)
Sepsis is a heterogeneous syndrome caused by a dysregulated host response during the process of infection. Neutrophils are involved in the development of sepsis due to their essential role in host defense. COVID-19 is a viral sepsis. Disfunction of neutrophils in sepsis has been described in previous studies, however, little is known about the role of microRNA-let-7b (miR-let-7b), toll-like receptor 4 (TLR4), and nuclear factor kappa B (NF-κB) activity in neutrophils and how they participate in the development of sepsis. In this study, we investigated the regulatory pathway of miR-let-7b/TLR4/NF-κB in neutrophils. We also explored the downstream cytokines released by neutrophils following miR-let-7b treatment and its therapeutic effects in cecal ligation and puncture (CLP)-induced septic mice. Six-to-eight-week-old male C57BL/6 mice underwent CLP following treatment with miR-let-7b agomir. Survival (n=10), changes in liver and lungs histopathology (n=4), circulating neutrophil counts (n=4), the liver-body weight ratio (n=4–7), and the lung wet-to-dry ratio (n=5–6) were recorded. We found that overexpression of miR-let-7b could significantly down-regulate the expression of human-derived neutrophilic TLR4 at a post-transcriptional level, a decreased level of proinflammatory factors including interleukin-6 (IL-6), IL-8, tumor necrosis factor α (TNF-α), and an upregulation of anti-inflammatory factor IL-10 in vitro. After miR-let- 7b agomir treatment in vivo, neutrophil recruitment was inhibited and thus the injuries of liver and lungs in CLP-induced septic mice were alleviated (p=0.01 and p=0.04, respectively), less weight loss was reduced, and survival in septic mice was also significantly improved (p=0.013). Our study suggested that miR-let-7b could be a potential target of sepsis.